Influence of institutional isomorphism on unethical pro-organizational behavior of construction teams based on the mediating effect of organizational routines - Zhang, Bing; Fang, Ting; Xia, Bo; Liu, Xueying (Journal of Civil Engineering and Management, 2026)
Unethical behavior that favors the organization at the expense of unethical conduct is considered an example of unconventional motivation. Unethical pro-organizational behavior (UPB) reduces the project quality and safety in the construction industry and may also lead to increased construction costs and investment losses. By conducting a crosslayer analysis and administering a questionnaire survey with 352 construction team employees, this study examines the influence of institutional isomorphism on UPB and the path between them. Moreover, the study explores the mediating effect of organizational routines. Results indicate that institutional isomorphism has different effects on implicit and explicit routines. Organizational routines play a crucial role in institutional isomorphism and UPB. Several mediating paths exist between institutional isomorphism and UPB. Furthermore, UPB is mainly implemented by strengthening the mediating effect of implicit routines and weakening that of explicit routines.